Hidrolisis Daun Sawit Menjadi Glukosa Dengan Variasi Konsentrasi Asam Fosfat (H3PO4) Dan Rasio Substrat-Pelarut - Boy Jansen Roberto Manik; Sri Rezeki Muria; Komalasari Komalasari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Indonesia, especially Riau is a palm oil producing region. The increase of plantation and palm oil production is directly proportional to the amount of waste produced. Increasing waste is not offset by the treatment of such waste as oil palm leaves waste. Oil palm leaves is a lignocellulosic material which can be used to make products, one of them is glucose which can be used to make bioethanol and others. This research is aims to determine the best concentration of phosporic acid (H3PO4) and substrate-solvent ratio in the oil palm leaves hydrolysis to produce high glucose levels. The process of glucose production from oil palm leaves is carried out in various stages, namely preparation of raw materials, acid pretreatment process, analysis of raw materials and pretreatment, hydrolysis and results analysis. Acid pretreatmentwas carried out at temperature of 80ᴼC, within 60 minutes using sulfuric acid 0,5%. Hydrolysis is done by mixing sulfuric acid 60% and phosphoric acid in ratio 30:70, which is the concentration of phosphoric acid (60%,65% and 70%) and substrate ratio (product of pretreatment) with solvent (1:3 and 1:4) becomes the independent variable. Hydrolysis process is done by mixing solvent and substrate and left during 16 hours at room temperature, then added distilled water and cooked at 100 ᴼC during 2 hours. The result of this research obtained the best condition of oil palm leaves hydrolysis is the ratio of substrate-solvent 1:2 and phosporic acid 70% with a glucose level is 1977,8619 mg/L.Keywords : Glucose, hydrolysis, phosphoric acid, oil palm leaves, sulfuric acid